Utility of anti-Mycobacterium tuberculosis antibody (ab905) for detection of mycobacterial antigens in formalin-fixed paraffin-embedded tissues from clinically and histologically suggestive extrapulmonary tuberculosis cases - Samuel Ofori Addo; Afua Owusua Darkwah Abrahams; Gloria Ivy Mensah; Bernice Anane Mawuli; Lydia Mosi; Edwin Kwame Wiredu; Kennedy Kwasi Addo (Heliyon, 2022)
Background: The detection of acid-fast bacilli in extrapulmonary tissue samples is challenging due to its paucibacillary nature. The present study assessed the utility of immunohistochemistry (IHC) using anti-Mycobacterium tuberculosis antibody (ab905) for detecting the presence of mycobacterial antigens in archived formalin-fixed paraffin-embedded (FFPE) tissues. Methods: FFPE tissues [surgical biopsies (n = 32) and post-mortem tissues (n = 8)] from clinically and histologically suggestive extrapulmonary tuberculosis (EPTB) cases at the Korle Bu Teaching Hospital, Accra, Ghana from 2015 to 2020 were stained with IHC (anti-Mycobacterium tuberculosis antibody) and Ziehl-Neelsen (ZN) stain. The staining outcomes of IHC and ZN were compared, and their sensitivity and specificity determined against histopathology as reference standard. Results: Lymph nodes were about 40% (16/40) of the samples analyzed. IHC stained positive in 43.8% (7/16) biopsies and 87.5% (4/5) post-mortem samples ranging from 43.8% (7/16) in lymph nodes to 80% (4/5) in gastrointestinal organs. The overall sensitivity for IHC was 52.50% (95% CI: 36.13%–68.49%) and 0% (95% CI: 0.00%–8.81%) for ZN. Specificity was 72.50% (95% CI: 56.11%–85.40%) and 75% (95% CI: 58.80–87.31%) for IHC and ZN respectively. Conclusions: IHC using anti-Mycobacterium tuberculosis antibody (ab905) can detect mycobacterial antigens in diverse range of paucibacillary extrapulmonary tissue sections. It is potentially a useful tool for the diagnosis of EPTB in FFPE tissues in a routine pathology laboratory.